Membership or Motivation: Exploring Reform Jewish Women’s Participation in Religious Education - Teresa L. Mareschal; E. Paulette Isaac (Adult Education Research Conference, 2006)
Members of Reform Judaism believe that as Jews they must study Jewish tradition. Reform Jewish Temples, national organizations and community centers have a long track record of offering adult learning opportunities. This study explored what motivates or deters women from participating in Reform Jewish adult education.
Keywords: Adult education participation; adult Jewish education; women